Integração entre os propósitos das novas gerações e das organizações: uma proposta baseada nos conceitos de espiritualidade nas organizações - Valle, Lisiane Cardoso do (Universidade do Vale do Rio dos Sinos, 2019)
The present study seeks to understand the elements of Spirituality and how these elements can contribute to the engagement between the purposes of new generations and organizations: a proposal based on the concepts of spirituality in Organizations. It was identified that through the concepts and elements of Spirituality in Organizations, through the connection of values and individual purposes with the environment, it creates the necessary understandings for the promotion of an organizational environment that educates happier and more engaged individuals with your work. In a complementary way, spirituality provides the appropriate environment to stimulate these engagement connections between the purposes of new generations and organizations, because their concepts consider that people develop from becoming aware of and connecting your inner world with your outside world. From the theoretical findings, an empirical research was carried out, based on a semi-structured interview script, involving 12 participants, representatives of small, medium and large companies from Porto Alegre and Grande Porto Alegre. Professionals that got involved in the research were in leadership positions and the new generations themselves. All organizations involved in the research have a solid organizational culture. The results found by the interviewees' perception showed that the new generations seek a job that can provide an alignment with their values, a greater purpose than only making money. They want to do their work with a purpose and seek companies whose values are aggregated with society and with the world in a bigger way. Another important factor in the interviews is the recurring response by the Educator Leader, a new concept of Leader that companies seek in order to contribute to the integration between the purposes of the new generations.
Keywords: Integração; Novas gerações; Espiritualidade nas organizações; Integration; New generations; Spirituality in organizations; ACCNPQ::Ciências Sociais Aplicadas::Administração